Hydrogeochemistry of the lower Kelantan Basin, Malaysia - Sefie, Anuar (2018)
Groundwater plays a crucial role in supporting the physical and economic development of any region, especially in areas that are experiencing shortage of surface water resources. Due to industrialization, population growth and intensive agriculture, the dependence on groundwater resources has increased dramatically from time to time resulting in quantity and quality deterioration, consequently, affecting human health and plant growth. A comprehensive hydrogeochemical study is essential in understanding the evolution of groundwater in a multi-layered aquifer system. The aims of this study were to construct a conceptual model, identify the factors controlling the chemistry of the groundwater, assess the hydrogeochemical facies of the groundwater, and evaluate the suitability of the groundwater for drinking and agricultural purposes. 101 groundwater samples were collected and analyzed for physico-chemical parameters such as the pH, the electrical conductivity (EC), the total dissolved solid (TDS), Ca2+, Mg2+, Na+, K+, HCO3 -, CO3 2-, Cl-, SO4 2-, NO3 -, Fe2+ and Mn2+. Based on lithological data correlation of exploration wells, three aquifer layers were delineated; a shallow, an intermediate and a deep. PCA demonstrated that Factor 1 (VF1) for the shallow aquifer represents 41.23% of the total variance. The variables Na+, Cl-, the TDS, the EC, Mg2+, and SO4 2- showed strong positive factor loadings and indicate the influence of remnant saltwater in the aquifer system. Factor 2 (VF2) which accounts for 13.23% of the total variance exhibited a strong positive loading for HCO3 - and suggests an origin from the weathering of carbonate. Factor 3 (VF3) was associated with 9.33% of the total variance and had strong positive loadings for Fe2+ and Mn2+, while NO3 - showed a strong positive loading in Factor 4 (VF4) representing 7.23% of the variance. The Fe2+ and Mn2+ in Factor 3 (VF3) are attributed to weathering of iron and manganese bearing minerals, whereas NO3 - is assigned to anthropogenic sources like sewage and fertilizer usage. The four principal components (VF1, VF2, VF3 and VF4) account for 71.11% of the total variance for the shallow aquifer. FA for the intermediate aquifer resulted in three significant factors accounting for 75.92% of the total variance. Factor 1 (VF1) demonstrated strong positive loadings for the TDS, the EC, Cl-, Na+, Mg2+, K+ and Ca2+ representing 53.73% of total variance, and attributed dissolution of minerals from seawater remnant. Factor 2 (VF2) which explained 14.55 % of the variance showed a strong positive loading for pH and a strong negative loading for Fe2+. This indicated the pH was affected due to enhanced dissolution and Fe2+ was assigned to weathering of iron bearing minerals. The variable of SO4 2- showed a strong negative loading in Factor 3 (VF3) that explained 7.64% of the total variance, and it is attributed to oxidation and dissolution of sulfate-rich marine deposits. For the deep aquifer, Factor 1 (VF1) showed strong positive loadings for Cl- , the EC, the TDS, Na+, Fe2+, K+, Mg2+ and Ca2+, and a strong negative loading for pH, accounting for 55.08% of the total variance. Factor 2 (VF2) accounted for 12.13% of the total variance, with strong positive loadings for carbonate that are explained by calcium carbonate weathering processes. Factor 3 (VF3) showed strong positive loadings for pH, Na+, K+ and Fe2+ and represented 8.39% of the total variance. This was attributed to the dissolution and weathering of rock forming minerals. Factor 4 (VF4) representing 7.38% of the total variance showed a strong negative loadings for SO4 2- reflecting oxidation and dissolution of sulfate-rich marine deposits. The abundance of the major cations followed the order: Na+ > Ca2+ > Mg2+ > K+, while that of anions was HCO3 - > Cl- > SO4 2- > CO3 2-. The prominent groundwater facies in the shallow aquifer are Ca-HCO3 and Na-HCO3 and indicate the presence of fresh water and mix-water types. The Na-HCO3 and Na-Cl are the main water types in the intermediate aquifer and exhibit the presence of mix-water and saltwater types. The Na-HCO3 is the dominant water type in the deep aquifer and is probably due to the consumption of H+ in the chemical weathering of feldspars to clay minerals. The Gibbs diagram stipulates that the groundwater in the aquifers are mostly affected by rock dominance, regardless of aquifer depth. Based on US Salinity Laboratory (USSL) diagram, the shallow groundwater samples fall in the C1-C3 and S1, and is suitable for irrigation of most crops. Samples from the intermediate aquifer plot in the C1-C4 and S1-S4 and are not suitable for irrigation of crops. The samples from deep aquifer fall in the C1-C3 and S1 and some samples are unsuitable for irrigation of crops. Some groundwater samples taken from the intermediate and the deep aquifers that fall into S4 zone are categorized as very high salinity hazard samples. The groundwater samples obtained from areas located more than 8 km from coast for all aquifers are suitable for crop irrigation. A high SAR value in the groundwater leads to the formation of an alkaline soil which reduces soil permeability due to hardening and compaction when dry. The physical structure of the soil crumbles and renders it unsuitable for plant growth. The study reveals that the groundwater quality from the shallow and the deep aquifers are better for domestic and agricultural purposes relative to groundwater from the intermediate aquifer for aquifer located less than 8 km from coast. These results provide a baseline data and offers insights on the status of groundwater quality in the Lower Kelantan Basin. The study also determined the factors controlling the quality of groundwater in each aquifer. Groundwater quality in the Lower Kelantan Basin is governed by anthropogenic activities and natural factors.